Forensic marketing: how to sharpen pharmaceutical brand strategy - Wolff, Neal (Henry Stewart Talks, 2025)
Forensic Marketing, Analysing drug/brand launch campaigns, Drug marketing, Entresto® launch campaigns, Thought leaders/key opinion leaders and high prescribers, Gaining early input from payers